A 23-Year-Old Woman with Cerebellopontine Tumor Angle Sectio Caesaria Trans-peritoneal Profunda Surgery Over Oligohydramnios Indication - Dina Paramita; Try Buana Tunggal Putera (JAI (Jurnal Anestesiologi Indonesia))
Background: Primary tumor are rarely found in pregnancy. Treatment for intracranial tumors in pregnant woman is a challenge for anesthesiologists, obstetricians and neurosurgeons. A large size cerebellopontine angle (CPA) tumor can suppress the brain stem structure and cause death if not treated immediately. This makes the way we treat patients, when the delivery time and the surgical intervention we choose to be quite difficult.